2009
DOI: 10.1111/j.1440-1681.2008.05103.x
|View full text |Cite
|
Sign up to set email alerts
|

HISTOPATHOLOGICAL AND SCINTIGRAPHIC COMPARISONS OF THE PROTECTIVE EFFECTS OF l‐CARNITINE AND AMIFOSTINE AGAINST RADIATION‐INDUCED LATE RENAL TOXICITY IN RATS

Abstract: 1. The aim of the present study was to compare the protective effects of L-carnitine and amifostine against radiation-induced late nephrotoxicity using technetium-99m diethylenetriaminepentaacetic acid scintigraphy and histopathological examination. 2. Seventy-one Albino rats were randomly divided into six groups as follows: (i) AMI + RAD (n = 15), 200 mg/kg, i.p., amifostine 30 min prior to irradiation (a single dose of 9 Gy); (ii) LC + RAD (n = 15), 300 mg/kg, i.p., L-carnitine 30 min prior to irradiation; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
(51 reference statements)
1
24
0
1
Order By: Relevance
“…4b, Table 2). Similar glomerular lesions have been described previously (Sieber et al 2009;Caloglu et al 2009). Kidney lesions were obvious in the cortex 64 d post-irradiation, but analysis revealed that deeper lesions developed between 64 and 104 d after irradiation, as shown by the increased histological score in the medulla between 64 and 104 d post-irradiation (Table 2).…”
Section: Evolution Of Body Weight In 12-gy and 14-gy Irradiated Rats supporting
confidence: 58%
“…4b, Table 2). Similar glomerular lesions have been described previously (Sieber et al 2009;Caloglu et al 2009). Kidney lesions were obvious in the cortex 64 d post-irradiation, but analysis revealed that deeper lesions developed between 64 and 104 d after irradiation, as shown by the increased histological score in the medulla between 64 and 104 d post-irradiation (Table 2).…”
Section: Evolution Of Body Weight In 12-gy and 14-gy Irradiated Rats supporting
confidence: 58%
“…Its protective effect in CDDP-induced renal and intestinal toxicity [11], gentamicin-induced nephrotoxicity [12], doxorubicin-induced nephrotoxicity [13], and chronic renal failure [14] has been demonstrated by various models. Although it has been recently reported that CAR and AMF have comparable and significant protective effects against radiation-induced nephrotoxicity in rats [15], their comparative effects against CDDP-induced nephrotoxicity have not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Intraperitoneal injections were made by dividing the abdomen into four quadrants on an imaginary midline and one perpendicular line at the level of the umbilical mark, L-carnitine and sterile saline were administered into the lower-left quadrant by using 1-ml syringes with a 26 G 3/8-inch needles. The selection of the 30-min interval between intraperitoneal L-carnitine administration and exposure to radiation was based on a previous experimental study 14 .…”
Section: Methodsmentioning
confidence: 99%
“…The body can endogenously synthesize about 10% of the L-carnitine it requires from lysine and methionine amino acids in the skeletal muscle, heart, liver, kidney, and brain; the remaining amount is generally obtained through diet 12,13 . Experimental models have demonstrated its radioprotective effects in the kidney, lens and cochlea, retina, brain, growing bone, testes, oral mucosa, small intestine and bone marrow [14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%